2016
DOI: 10.1042/bst20150223
|View full text |Cite
|
Sign up to set email alerts
|

Role of inorganic polyphosphate in mammalian cells: from signal transduction and mitochondrial metabolism to cell death

Abstract: Inorganic polyphosphate (polyP) is a polymer compromised of linearly arranged orthophosphate units that are linked through high-energy phosphoanhydride bonds. The chain length of this polymer varies from five to several thousand orthophosphates. PolyP is distributed in the most of the living organisms and plays multiple functions in mammalian cells, it is important for blood coagulation, cancer, calcium precipitation, immune response and many others. Essential role of polyP is shown for mitochondria, from impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 42 publications
0
51
0
1
Order By: Relevance
“…Very recently, a role for polyP in post-translational modification of Lys residues in proteins has been reported 2. In complex organisms, as humans, this polymer is involved in many diverse functions such as blood coagulation, bone formation, immune response, regulation of calcium level in mitochondria, or neurotransmission (see 3 and references herein). In addition, polyP is used in diverse industrial processes, including water treatment, and as fertilizer in agriculture 4.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, a role for polyP in post-translational modification of Lys residues in proteins has been reported 2. In complex organisms, as humans, this polymer is involved in many diverse functions such as blood coagulation, bone formation, immune response, regulation of calcium level in mitochondria, or neurotransmission (see 3 and references herein). In addition, polyP is used in diverse industrial processes, including water treatment, and as fertilizer in agriculture 4.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of polyP in cellular organelles and vesicles can indicate a specific signaling function. In this study, we found that ∌39% of the total pool of intracellular polyP in astrocytes is located in mitochondria (Figure 1) where it plays a role in bioenergetics (Angelova, Baev, et al, 2016; Pavlov et al, 2010) and calcium handling (Abramov et al, 2007; Baev et al, 2017; Elustondo et al, 2016). The level of polyP in mitochondria has been previously shown to be dependent on the metabolic state and the age of the cells (Pavlov et al, 2010).…”
Section: Discussionmentioning
confidence: 63%
“…organisms. In prokaryotes and lower eukaryotes polyP have been found to plays multiple roles, including those similar to ATP (Angelova, Baev, Berezhnov, & Abramov, 2016;Holmstrom et al, 2013). In mammalian cells, polyP is involved in the mechanisms of cell death, blood coagulation, bone formation, mitochondrial metabolism, and calcium handling (Abramov et al, 2007;Angelova, Baev, et al, 2016;Morrissey, Choi, & Smith, 2012;Pavlov et al, 2010).…”
mentioning
confidence: 99%
“…PolyP is also detected in mammalian cells (Kumble & Kornberg, 1995;Stotz et al, 2014), and intracellularly in nuclei (Ali, Wathes, Swali, Burns, & Burns, 2017), mitochondria (Abramov et al, 2007) (Angelova, Baev, Berezhnov, & Abramov, 2016), and lysosomes (Angelova et al, 2014). The number of studies reporting the effects of polyP as a supplemental nutrient has been increasing for humans, but the physiological functions and metabolic pathways of polyP are less well understood in mammals.…”
Section: Introductionmentioning
confidence: 99%